PI-STA cascade controller tuning for active power filter applications - R. Terán; J. Pérez; J. Beristáin; V. Cárdenas (Revista Iberoamericana de Automática e Informática Industrial RIAI)
Typically, the control scheme of the active power filter corresponds to a cascade controller, which consists of an outer loop for dc voltage regulation and an inner loop for the tracking of a reference current. Each control loop must be associated with controllers that allow a fast convergence to the established references. This paper presents a cascade controller for active power filter applications, employing a proportional-integral (PI) controller for the external loop, and the super-twisting algorithm (STA) for the internal loop, where the union of both controllers is called PI-STA cascade controller. On the one hand, a step response analysis for the estimation PI gains is carried out. On the other hand, the STA tuning takes place from considering the similarity between the structures of STA with a PI. In order to validate the methodology tuning consistency simulation and experimental results are presented.